Occupational and non-occupational allergic contact dermatitis and quality of life: a prospective study - Catiussa Spode Brutti; Renan Rangel Bonamigo; Taciana Cappelletti; Gabriela Mynarski Martins-Costa; Ana Paula Salin Menegat (Sociedade Brasileira de Dermatologia, 2013)
Attempted to evaluate and compare the impact on quality of life of occupational and non-occupational ACD and to identify the most frequently involved allergens. A quality of life questionnaire was applied. We noted moderate impact on the quality of life of both groups, without a statistical difference. Our study corroborates previous general data on the prevalence of nickel sulphate and paraphenylenediamine as the most common allergens. Potassium bichromate was shown to be one of the main occupational allergens and thimerosal as the main non-occupational allergen in our sample.